Recent Advances in the Synthesis of Coumarin Derivatives via Pechmann Condensation - S. Zambare, Abhay; A. Kalam Khan, Firoz; P. Zambare, Sureshchandra; D. Shinde, Shantanu; N. Sangshetti, Jaiprakash (Current Organic Chemistry, 2016)
The Pechmann condensation is the formation of coumarin derivatives from phenols and a carboxylic acids or esters containing a β-carbonyl group under acidic conditions. The reaction has attracted a great deal of attention because of the biological significance of coumarins derivatives. As a result, the synthesis of coumarin and its derivatives have been an attractive goal for the chemist. The present review is focused on brief aspects of the synthesis of coumarin derivatives from phenols and a carboxylic acids or esters containing a β-carbonyl group under acidic conditions using various catalysts.
Keywords: ionic liquids